2010
DOI: 10.1186/1471-2148-10-29
|View full text |Cite
|
Sign up to set email alerts
|

Ancient origin of a Western Mediterranean radiation of subterranean beetles

Abstract: BackgroundCave organisms have been used as models for evolution and biogeography, as their reduced above-ground dispersal produces phylogenetic patterns of area distribution that largely match the geological history of mountain ranges and cave habitats. Most current hypotheses assume that subterranean lineages arose recently from surface dwelling, dispersive close relatives, but for terrestrial organisms there is scant phylogenetic evidence to support this view. We study here with molecular methods the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
190
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 152 publications
(215 citation statements)
references
References 58 publications
12
190
0
13
Order By: Relevance
“…A similar rate was also found in other studies comparing more closely related species of Coleoptera and using different combinations of mitochondrial genes, both ribosomal and protein-coding (e.g., Leys et al, 2003;Pons and Vogler, 2005;Pons et al, 2006;Balke et al, 2009;Ribera et al, 2010).…”
Section: Nucleotide Substitution Rates and Agessupporting
confidence: 87%
See 1 more Smart Citation
“…A similar rate was also found in other studies comparing more closely related species of Coleoptera and using different combinations of mitochondrial genes, both ribosomal and protein-coding (e.g., Leys et al, 2003;Pons and Vogler, 2005;Pons et al, 2006;Balke et al, 2009;Ribera et al, 2010).…”
Section: Nucleotide Substitution Rates and Agessupporting
confidence: 87%
“…In a study with closely related species of Adephaga, Pons et al (2005) found slower rates for cox1 (0.0167 versus 0.0861 subs/s/my/l) but similar rates to those estimated here for cob (0.0211 versus 0.0171 subs/site/my/l, Table 4). Ribera et al (2010) also found slower cox1 rates (0.02 subs/site/my/l) for a group of Polyphagan cave beetles in a time interval of ~40 MY, estimated with a single GTR+I+G model. A similar study performed on complete mitochondrial genomes of 27 salamander species, and using partitioning by codon sites showed a similar trend (Mueller, 2006).…”
Section: Nucleotide Substitution Rates and Agesmentioning
confidence: 70%
“…To establish a temporal framework for the origin and evolution of the A. brunneus complex we used the mitochondrial genes only, for which there are recent calibrations for different families of Coleoptera with very homogeneous estimations for the rate of a combination of protein coding and ribosomal mitochondrial regions, calibrated with fossils and different biogeographic events [39][40][41]. As a prior we used a normal distribution with an average combined rate of 0.01 substitutions/site/million years (MY) and a standard deviation of 0.001, with other settings identical to the above analysis.…”
Section: General Phylogenetic Relationshipsmentioning
confidence: 99%
“…The major beetle families found in caves are ground beetles (Carabidae: Trechinae), followed by small carrion beetles (Cholevidae or Cholevinae within Leiodidae) and rove beetles (Staphylinidae) (Moldovan, 2005) with large distributions in the palearctic and nearctic ecozones. In addition, a large diversity of aquatic troglobiotic diving beetles (Dytiscidae) has been discovered in Australia (Faille et al, 2010;Leys and Watts, 2008;Leys et al, 2003;Ribera et al, 2010). The Coleoptera are thus an ideal study group to explore the breadth of cave-adaptive states.…”
Section: Introductionmentioning
confidence: 99%